Illegal Fishing and Maritime Security: Historical and Contemporary Challenges in Namibia - Iroanya, Richard Obinna; Simataa, Charlene (Scientia Militaria - South African Journal of Military Studies, 2024)
The study on which this article reports argued that illegal fishing activities in the Namibian territorial waters and exclusive economic zones have implications for maritime security. The study traced the problem of illegal fishing in the country back to colonial times and linked it directly to foreign vessels. The intrusion of foreign vessels into Namibian waters received little interest – or if at all – in terms of the protection of ocean resources by the colonial administration coupled with a lack of regulatory frameworks. It was noted that the pattern of illegal fishing established during colonial times has continued into the present with several consequences. Illegal fishing affects maritime security in Namibia in five main dimensions, namely projection of military power at sea, protection of the marine environment, economic growth, development, and human security. These dimensions of maritime security are integrally linked and mutually reinforcing. It was thus shown that the limitation of sea patrols by the Namibian Navy and the Ministry of Fisheries and Marine Resources due to financial constraints caused by illegal fishing activities has a negative influence on the marine environment in terms of destruction and depletion of fish resources. Depletion of fish stocks results in loss of revenue and loss of jobs for coastal community dwellers. Combating illegal fishing is necessary if the marine resources are to be protected and make a significant contribution to the Namibian state. To combat the challenge of illegal fishing, improvement and strengthening of existing mechanisms, international collaboration, cooperation, and coordination between maritime security agencies, and continued engagement with neighbouring states were considered necessary.